Silicon can attenuate glyphosate-induced stress in young Handroanthus albus by improving photosynthetic efficiency and decreasing cellular electrolyte leakage - Milton Garcia Costa; Rafael de Amorim Cordeiro; Júlia Karoline Rodrigues das Mercês; Liedson Silva de Medeiros; Alexandre Moraes Cardoso; Renato de Mello Prado; Davie M. Kadyampakeni; Maria Thalia Lacerda Siqueira; Jonas Pereira de Souza Junior (Scientific Reports)
Abstract The extensive use of glyphosate, while effective in weed control, poses significant risks to non-target plant species such as Handroanthus albus (yellow Ipe), an important species in tropical sustainable forestry. This study aimed to assess the impact of glyphosate on young Ipe plants and to investigate the protective role of silicon (Si) supplementation. Increasing glyphosate concentrations were found to induce heightened cellular electrolyte leakage and reduced concentrations of photosynthetic pigments in young Ipe leaves. Glyphosate exposure also compromised photosynthetic efficiency, resulting in decreased leaf biomass production. Conversely, supplemental applications of Si, applied via root and foliar routes, significantly increased Si accumulation in young Ipe leaves and mitigated the adverse effects of glyphosate. Silicon treatment decreased electrolyte cellular leakage by enhancing antioxidant defenses, particularly through elevated flavonoid and anthocyanin levels, and preserved photosynthetic efficiency. Si-treated plants maintained higher chlorophyll a concentration and exhibited improved photochemical efficiency, even under moderate rates of glyphosate stress. Consequently, Si application led to increased leaf dry mass, particularly at moderate glyphosate concentrations, highlighting its role in enhancing the resilience of young Ipe plants to moderate herbicide-induced stress. Incorporating Si into sustainable forestry practices could enhance the resilience of key species, supporting reforestation and afforestation efforts in glyphosate-prone environments.